Tari Topeng Nindak-Nandak Sebagai Tari Pertunjukan Di Sanggar Margasari Kacrit Putra - Sipayung, Desisca Thalia Rut Debora; Sudiasa, Ida Bagus Ketut; Haerudin, Deden (Jurnal Pendidikan Tari, 2024)
Topeng Nindak-Nandak Dance is a creation of Betawi Mask Dance which was produced by Sanggar Margasari with dance director Selvie Ervieliani in 2009. This research is focused on: How is the form and meaning of Topeng Nindak-Nandak Dance as a performance dance at Studio Margasari Kacrit Putra. The theory used in this study is the theory of semiotics by Charles Shanders Peirce. Triadic theory is divided into several levels, firstness, secondness and thirdness. This study uses a descriptive qualitative approach. The data collection strategy was carried out by observation, literature study and interviews which were then processed according to the research objectives. Based on the results of the analysis conducted on the Nindak-Nandak Mask Dance at the Margasari Kacrit Putra Studio, the form and meaning of the dance are interrelated in one unified whole. The Nindak-Nandak Mask Dance is a performance dance that is suitable and worthy of being performed as a work that can be enjoyed in terms of the workmanship, value and meaning contained therein. There are the main elements of dance performances: Gestures, music, costumes, make-up, lighting and decorations, choreography, expressions and emotions that have been designed to the maximum extent possible. Keywords: Form, Symbolic Meaning, Nindak-Nandak Mask Dance, Performing Dance, Semiotics